Taking the goalkeeper's side in association football penalty kicks - Casals, M.; Martinez, J. A. (International Journal of Performance Analysis in Sport, 2013)
Approximately 70% of penalty kicks in men's professional football are scored, hence being decisive in increasing the chances of winning, since matches have only 2.5 goals on average. This study assesses the improving chances for the goalkeeper to save penalty kicks, using actual shot speeds in computer simulation and considering actual and experimental data. Simulated kicks were directed at the goal divided in nine areas. The goalkeeper's movement was chosen to start at five different times before, at and after the instant of the kicker's impact on the ball. Chances of saving were analysed through logistic regression taking into account area of the goal, ball speed and moment of goalkeeper's reaction. Saves were found to depend essentially on the beginning of the goalkeeper's motion according to the area. In the central areas of the goal, saves were statiscally independent of ball speed and time of reaction. The goal region further away from the centre, where real shots are frequently saved, presented highest dispersion. This suggests that saves depend mainly on the goalkeeper's reaction time but also on the ball speed. Finally, chances are low (but not inexistent) near the posts.